Kekerasan: Wujud Kehampaan Eksistensi Sebuah Tinjauan Etis atas Pemikiran Erich Fromm - Sihotang, Kasdin (Jurnal Etika Respons, 2009)
Erich Frommâs analysis of the root of violence in The Anatomy of Human Destructiveness can be seen as a starting point to understand the nature of violence. He contends that violence is not existential but exists as a result of a negative condition that prohibits someone to grow according to his own choice. According to this definition, human aggression is neutral. It can be identified as defensive if it is used to save life, and as destructive one if it destroys the life itself and against the human values. Fromm explains that the progress of technology and science are the main factors that cause modern man, that is called cybernetic man, to act destructively in their life.